Organotypic culture of breast tumor explants as a multicellular system for the screening of natural compounds with antineoplastic potential - Carranza Torres, Irma Edith; Guzmán Delgado, Nancy Elena; Coronado Martínez, Consuelo; Bañuelos García, José Inocente; Viveros Valdez, José Ezequiel; Morán Martínez, Javier; Carranza Rosales, María del Pilar (2015)
Breast cancer is the leading cause of death in women worldwide. The search for novel compounds with antitumor activity, with less adverse effects and higher efficacy, and the development of methods to evaluate their toxicity is an area of intense research. In this study we implemented the preparation and culture of breast tumor explants, which were obtained from precision-cut breast tumor slices. In order to validate the model we are proposing to screen antineoplastic effect of natural compounds, we selected caffeic acid, ursolic acid, and rosmarinic acid. Using the Krumdieck tissue slicer, precision-cut tissue slices were prepared from breast cancer samples; from these slices, 4 mm explants were obtained and incubated with the selected compounds. Viability was assessed by Alamar Blue assay, LDH release, and histopathological criteria. Results showed that the viability of the explants cultured in the presence of paclitaxel (positive control) decreased significantly (